The knowledge, awareness and practices of radiation safety amongst orthopaedic surgeons - Louis W.A. van Papendorp (South African Journal of Radiology, 2020)
Background: Fluoroscopic imaging in orthopaedic theatres is increasing, with added risk to the orthopaedic surgeon who is increasingly being exposed to ionising radiation. It is thus crucial for orthopaedic surgeons to have a working knowledge of radiation safety. In spite of these concerns, however, many orthopaedic surgeons do not receive standard training in radiation safety.